PECULIARITIES OF PREPARATION AND PRESENTATION OF FINANCIAL STATEMENTS IN RAILWAY TRANSPORT ENTERPRISES (World Economics and Finance Bulletin, 2023)
The article is in accordance with the IFRS, in railway enterprises financial reporting methods, The shortcomings and advantages of the reports prepared on the basis of IFRS, its completeness and the order of presentation are revealed
Keywords: Railway enterprise; prospective; transformation